Navigating Teenage Motherhood: Challenges of Adolescent Mothers in Northern Samar, Philippines - Donoga, Danhill (Journal of Interdisciplinary Perspectives, 2025)
Teenage motherhood remains a pressing yet underexamined concern in the Philippines, particularly in impoverished and underserved provinces like Northern Samar. Despite policy attention, the lived experiences of adolescent mothers navigating school, parenting, and social stigma are insufficiently documented. This study addresses the gap by exploring the academic, caregiving, and stigma-related challenges faced by adolescent mothers aged 15–19 enrolled in public secondary schools in Northern Samar from 2022 to 2024. Employing an embedded concurrent mixed-methods design, the quantitative strand utilized a validated survey (Cronbach’s α = 0.914) administered to 335 participants, while the qualitative strand analyzed thematic insights from in-depth interviews. Quantitative results revealed serious challenges in balancing school and caregiving (M=3.84), emotional strain from parenting duties (M= 3.89), and stigma, especially from educators (M=4.01). Thematic analysis highlighted four major organizing themes: Silent Emotional Suffering and Identity Strain, Internalized Shame and Disconnection, Economic Fragility and Sacrificial Living, and Physical Depletion and Untreated Illness. These were clustered under the global theme, The Burdened Resilience of Teenage Mothers in the Margins, revealing that resilience among adolescent mothers often emerges from necessity in the absence of structured support. The study concludes that systemic interventions—such as flexible schooling, psychosocial care, and financial assistance—must be designed to affirm the dignity and developmental needs of young mothers, rather than merely accommodate them. These findings inform adolescent-responsive educational and social policies to create inclusive spaces where teenage mothers can thrive academically and emotionally, not despite motherhood, but through the experience of it.